Combined use of irinotecan and p53 activator enhances growth inhibition of mesothelioma cells. Issue 11 (5th October 2020) - Han, Bo; Lee‐Okada, Hyeon‐Cheol; Ishimine, Momoko; Orita, Hajime; Nishikawa, Keiko; Takagaki, Tetsuya; Kajino, Kazunori; Yokomizo, Takehiko; Hino, Okio; Kobayashi, Toshiyuki
Abstract : Malignant mesothelioma (MM) is an aggressive malignant neoplasm which rapidly invades pleural tissues and has a poor prognosis. Here, we explore enhancement of the effect of irinotecan [camptothecin‐11 (CPT‐11)] by the p53‐dependent induction of carboxylesterase 2 (CES2), a CPT‐11‐activating enzyme, in MM. The level of CES2 mRNA was greatly increased on treatment with nutlin‐3a. A combination of CPT‐11 and nutlin‐3a inhibited the growth of MM cells more effectively than either drug alone. Knocking down CES2 in MM cells reduced the effect of the drug combination, and its forced expression in MESO4 cells enhanced the growth inhibitory activity of CPT‐11 in the absence of nutlin‐3a. Enhancement of the growth inhibitory activity of CPT‐11 by nutlin‐3a suggests a possible new combinatorial MM chemotherapy regimen. Abstract : We found that the growth inhibitory effect of irinotecan (CPT‐11) on mesothelioma (MM) cells was enhanced by nutlin‐3a (a p53 activator). Nutlin‐3a induced carboxylesterase 2 (CES2), a CPT‐11‐activating enzyme. Knockdown and forced expression of CES2 confirmed its role in the combined efficacy. The compound use of CPT‐11 and p53 activators might be suitable for development into a potential new MM chemotherapy regimen.